HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PENGOBATAN ANTIRETROVIRAL (ARV) PADA PENDERITA HIV DAN AIDS (ODHA) DI KLINIK VCT RS St. ELISABETH BLOK II LUBUK BAJA BATAM - Ditte Ayu Suntara; Dedy Siska; Tiorisne Rinna Wati Sinaga (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms that arise from infection with Human Immunodeficiency Virus (HIV). Antiretroviral therapy (ARV) is therapy for HIV / AIDS patients by taking drugs for the rest of their lives. Adherence to taking medication is one important aspect in assessing the success of ARV therapy. The virus in the body of people with HIV and AIDS can not get out, so a person must undergo ARV treatment for life and on time. A tight schedule of ARV treatment is expected to be able to suppress the amount of virus in the body. If it is not compliant then the drug will become resistant to the body. One of the factors that influence adherence to taking medication is family support. Therefore this study aims to determine the relationship of family support to the adherence of antiretroviral treatment (ARV) in people with HIV and AIDS at VCT Clinic in Santa Elisabeth Block II Lubuk Baja. Method. Quantitative research using the cross sectional study design. The population in this study amounted to 60 people and a sample of 37 people with a sampling technique that is incidental sampling. Measuring instruments in this study used a questionnaire. The statistical test used is the chi-square test with significance level (α = 0.05.) Results. As many as 59.5% of sufferers received support from families with obedience to treatment. More than 59.5% were obedient and received support from families. This study shows that there is a relationship between family support for ARV treatment adherence in PLWHA at VCT Clinic. Santa Elisabeth Blok II Lubuk Baja (p = 0,000). From the results of this study it can be concluded that family support affects the level of ARV treatment adherence in HIV / AIDS sufferers.